Temporary Closure for Gastroschisis Using Everyday Disposable Medical Devices: A Literature Review - Ahmad Razi Maulana Alnaz; Erjan Fikri; Zulham Yamamoto; Fini Meirisa Alnaz (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Gastroschisis is a life-threatening congenital abdominal wall defect requiring immediate surgical intervention at birth. In resource-limited healthcare settings, the availability of specialized silo devices for staged abdominal closure is frequently constrained by economic and logistical barriers. The use of everyday disposable medical devices as low-cost alternatives has gained increasing attention as a pragmatic approach to improving neonatal surgical outcomes in such environments. Objective: This literature review aims to synthesize available evidence on the use of disposable medical devices as alternative silo substitutes for temporary gastroschisis closure, evaluating their clinical applicability, safety profile, cost-effectiveness, and relevance to nursing care in low-resource neonatal settings. Methods: A systematic narrative literature review was conducted using databases including PubMed, Scopus, ScienceDirect, Springer, and Wiley Online Library. Studies published between 2015 and 2026 examining gastroschisis management, temporary abdominal closure techniques, improvised silo alternatives, and neonatal surgical outcomes were included. A total of 42 articles met inclusion criteria after screening and critical appraisal. Results: Evidence from multiple studies supports the feasibility and relative safety of improvised silo construction using readily available disposable materials, including urologic drainage bags, intravenous fluid bags, bowel irrigation sleeves, and sterile surgical gloves, particularly in settings where commercial silos are unavailable. Outcomes including bowel reduction time, wound infection rates, time to primary closure, and mortality were comparable to those achieved with commercial spring-loaded or sutured silos in several reports. Multidisciplinary neonatal nursing care was identified as a critical determinant of postoperative success. Conclusion: Everyday disposable medical devices represent a viable and cost-effective approach to temporary gastroschisis closure in resource-limited environments. Standardized protocols, rigorous infection control practices, and multidisciplinary collaboration are essential to optimize outcomes. Further high-quality prospective studies are needed to establish evidence-based guidelines for improvised closure techniques. Keywords: gastroschisis; temporary abdominal closure; disposable medical devices; neonatal surgery; resource-limited settings